P1–206: The search for a successful cognitive aging endophenotype in the offspring of very elderly (90+) nondemented probands in a founder population - Edland, Steve (2006)
Ascertaining families with demonstrable successful cognitive aging might help reveal rare genes associated with good cognitive functioning into very late old age. Given the genetic complexity of this desirable condition, however, validated cognitive endophenotypes (i.e., traits lying midstream between a gene and a genetically complex condition of interest) will be required for open ended gene finding strategies. Delayed recall in particular is a promising candidate endophenotype because it has shown strong heritability in AD proband families and delayed recall impairment has predicted the development of AD. Objective(s) To identify cognitive endophenotypes for successful cognitive aging in a founder population. Methods Delayed recall, along with other tests of cognitive functions, were assessed in 27 very elderly (age 90+) nondemented (VEND) probands and 47 of their aged 60+ offspring. The families were ascertained from the Central Valley of Costa Rica (CVCR), a founder population. Two sets of CVCR comparison groups were also assessed: 1) Very elderly (aged 90+) demented (VED) probands (n=13) and their age 60+ offspring (n=28); 2) Young (aged 60–70) nondemented elderly (YND; n=15) and their age 60+ siblings (n=17). Results VEND offspring, VED offspring, and YND sibling groups did not significantly differ with respect to age, sex, or years of education. Using a random effects model controlling for sex and education, delayed recall was significantly better among VEND offspring than YND siblings(P<0.005) and VED offspring (P<0.05). In addition, there were significant group by education interactions such that fewer years of education was associated with lower delayed recall scores in the YND siblings (P<0.005) and VED offspring (P<0.05), but education had no effect on VEND offspring. Similar albeit nonsignificant relationships were observed with age. Conclusions The VEND offspring had higher levels of delayed recall than the VED offspring and YND siblings. In addition, whereas low education was associated with poorer performance in delayed recall in two comparison groups, no such association was present in VEND offspring. These results are consistent with the hypothesis that delayed recall in VEND offspring is a state independent trait and might be a useful endophenotype for successful cognitive aging.